Understanding Voltage and Frequency Effects on Dielectrophoretic Forces in Microchannel System - Khazanna; Iswardy, Edwar; Yusibani, Elin (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
This study presents an innovative pedagogical tool for teaching dielectrophoresis (DEP) and electrokinetics. We developed a cost-effective lab-on-chip device featuring oblique and V-shaped microelectrode arrays within microchannels to demonstrate electric field effects on biological particles in real-time. The device utilizes copper and indium tin oxide (Cu-ITO) microelectrodes with double-sided tape insulators to create controlled microenvironments. Red blood cells suspended in deionized water and EDTA medium (conductivity: 1.5 S/m) serve as model bioparticles for visualization experiments. We manipulate sinusoidal AC signals (5-15 Vpp) while observing particle behavior through microscopy with charge-coupled device (CCD) recording capabilities. The hands-on approach enables direct observation of how voltage amplitude and frequency affect particle polarization and movement, bridging theoretical concepts with experimental reality. The results showed significant improvement in conceptual understanding of electric fields, force interactions, and bioelectronics applications compared to traditional lecture-based instruction. This educational tool addresses key learning objectives in electromagnetism and biophysics by providing immediate visual feedback of abstract concepts. The device's simplicity enables integration into existing laboratory curricula while promoting active learning, scientific inquiry, and critical thinking. The approach demonstrates practical applications of physics principles in biotechnology and medical diagnostics, enhancing student engagement and career relevance. This work contributes to physics education research by offering a scalable, low-cost method for teaching complex electrokinetic phenomena through direct experimentation.